Planning for Effective English Learning: The Role of Teacher’s Lesson Plans in Junior High Schools - ST Marhana Rullu; Marni Bawawa (Lembaga Riset dan Inovasi Almatani, 2026)
Lesson plans play an important role in guiding teachers during the teaching and learning process. A well-prepared lesson plan helps teachers organize learning objectives, classroom procedures, and student activities effectively. This study aims to explore the role of a teacher’s lesson plan in supporting English learning activities at Junior High School of Masama sub-district in Banggai Regency. This study employed a qualitative descriptive approach. The subject of this research was an English teacher, and the data were collected through interviews, classroom observations, and documentation of the teacher’s lesson plan. The findings indicate that the teacher’s lesson plan contains structured components that guide classroom activities, including learning objectives, learning materials, classroom procedures, and student activities aligned with the instructional goals. The lesson plan also helps the teacher manage classroom time and organize learning activities more effectively. Furthermore, the lesson plan functions as a guideline that assists teachers in implementing learning strategies and evaluating the learning process through reflection. The results also show that student activities in the classroom are carried out in accordance with the learning objectives and learning materials prepared in the lesson plan. Therefore, the study concludes that the teacher’s lesson plan plays an essential role in supporting English learning activities and facilitating the teaching and learning process in the classroom. These findings suggest that teachers should design well-structured lesson plans to improve the effectiveness of English learning activities in junior high school classrooms.